Mitigation of power quality issues for grid connected photo voltaic system using soft computing techniques - Pragathi, B.; Nayak, Deepak Kumar; Poonia, Ramesh Chandra (Journal of interdisciplinary mathematics, 2020)
Now a days Alternating Current distribution and transmission systems are suffering from many power qualities issues, mainly due to the presence of complex equipment in the residential, commercial, industrial applications. Power quality issues in distribution systems are classified as current-based and voltage-based quality problems. Complex Power Devices and distribution static compensators (D-STATCOM) are used to compensate for current-based power issues. The number of current-based power quality problems are unbalanced currents, undesired power factor, increased neutral current, and poor voltage regulation. Therefore, depending upon the problem, the configuration of the DSTATCOM is selected in the practice. This paper focuses on the control algorithms: Lorentzian adaptive filter, discrete adaptive filter, neural network least mean square and quasi newton control algorithms, for controlling shunt compensator (D-STATCOM) for compensating power issues, reactive power, unity power factor and load balancing under linear and non-linear load conditions with zero voltage regulation by maintaining constant capacitor voltage (VDC) and eliminate harmonic currents at point of common coupling by proportional-integral controller. In the proposed system MPPT is obtained by DC converter and the power quality issues are further analyzed in the existence of harmonics either in the currents or voltages. The DSTATCOM-control algorithms based solar Photo Voltaic system is simulated in MATLAB along with SIMULINK.